Ice hockey players using a weighted implement when training on the ice: a randomized control trial - Stark, T. W.; Tvoric, B.; Walker, B.; Noonan, D.; Sibla, J. (Research Quarterly for Exercise and Sport, 2009)
The purpose of this study was to investigate the potential for improving hockey players'performance using a weighted implement on the ice. Forty-eight players were tested using a grip strength dynamometer They also were assessed on their abilities to stick-handle. The participants were randomly placed into a control or research group. The conditioning drills were performed for 10-15 min 3 days/week for 6 weeks. Use of the weighted implement resulted in a significantly enhanced grip strength endurance and stick-handling ability (p < .05). Using weighted implements prior to a regular ice hockey training session may be of benefit to young hockey players to enhance their grip strength endurance and stick-handling abilities.